2020
DOI: 10.1101/2020.10.27.355479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive modeling of virus inactivation by UV

Abstract: Disinfection strategies are commonly applied to inactivate pathogenic viruses in water, food, air, and on surfaces to prevent the spread of infectious diseases. Determining how quickly viruses are inactivated to mitigate health risks is not always feasible due to biosafety restrictions or difficulties with virus culturability. Therefore, methods that would rapidly predict kinetics of virus inactivation by UV254 would be valuable, particularly for emerging and difficult-to-culture viruses. We conducted a rapid … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Thanks to this transition, those electrons were able to conduct a relaxation and overcame the barrier, and further resulted in physicochemical reactions (such as the covalent bond formation of the cyclobutane pyrimidine dimers (CPDs) or the cross-linking between pyrimidine and proteins) 43,44 . Furthermore, the DUV disinfection was a continuous process involving multiple photons, and products from the physicochemical reactions were more stable on energy (because the formed covalent bond is significantly more stable than the initial hydrogen bonding) 45 . At the same time, the energy of the barrier would increase for the subsequent reactions when more physicochemical reactions happened.…”
Section: Preliminary Test For the Effect Of Cryogenic Environment On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to this transition, those electrons were able to conduct a relaxation and overcame the barrier, and further resulted in physicochemical reactions (such as the covalent bond formation of the cyclobutane pyrimidine dimers (CPDs) or the cross-linking between pyrimidine and proteins) 43,44 . Furthermore, the DUV disinfection was a continuous process involving multiple photons, and products from the physicochemical reactions were more stable on energy (because the formed covalent bond is significantly more stable than the initial hydrogen bonding) 45 . At the same time, the energy of the barrier would increase for the subsequent reactions when more physicochemical reactions happened.…”
Section: Preliminary Test For the Effect Of Cryogenic Environment On ...mentioning
confidence: 99%
“…6(a), the inactivation of (+) single-stranded RNA viruses were mainly caused by the formation of UU (uracil/uracil) and UC (uracil/cytosine) dimers after the UV radiation. The published literature has demonstrated that these formed CPDs were relatively stable and required much higher excitation energy to initiate the photo-reversibility process back to their original monomer pyrimidines 45 . The possibility of dimers formation was related to the number of Cs, Us, UUs, and UUUs in the gene sequence 46 .…”
Section: Preliminary Test For the Effect Of Cryogenic Environment On ...mentioning
confidence: 99%
“…Three coronaviruses have been identified that cause more serious, sometimes fatal diseases in humans: SARS-CoV, MERS-CoV (cause of Middle East respiratory syndrome, MERS), and SARS-CoV-2. The structural similarity of these viruses, including their relatively large genomes, suggests that they should all be susceptible to inactivation by exposure to UV-C radiation and that their UV-C dose-response behaviors should be similar [ 10 15 ].…”
Section: Dose-response Data For Coronavirusesmentioning
confidence: 99%
“…Rockey et al . [ 15 ] conducted a review of the literature related to UV 254 dose-response behavior of viruses. For positive-sense, single-stranded RNA viruses, which include the coronaviruses, they developed a multiple linear regression model that yielded the lowest root-mean-squared relative prediction error (RMSrPE) based on the following variables: number of cytosines, uracils, uracil doublets, and uracil triplets.…”
Section: Model Predictions Of Sars-cov-2 Sensitivity To Uv ...mentioning
confidence: 99%